Stress Coping with Aggressive Driving Behavior among Generation Z in The Motorcycle Community - Alfi, Alfani; Dicky Listin Quarta; Lita Ariani (Fakultas Psikologi, Universitas Islam Negeri (UIN) Ar Raniry Banda Aceh, 2025)
Traffic accidents are the leading cause of death, particularly among Generation Z, with aggressive driving behavior being one of the main contributing factors. This behavior is often associated with low stress coping skills. This study aims to examine the relationship between stress coping and aggressive driving behavior. This study employs a quantitative correlational method, utilizing the Aggressive Driving Behavior Scale (ADBS) and Ways of Coping Stress instruments. The sample was selected using purposive sampling, comprising 100 Generation Z participants from a motorcycle community. Data analysis using Spearman’s rho correlation test showed a coefficient of -0.598 with a p-value < 0.001. This result indicates a strong negative relationship: the better an individual manages stress, the lower their aggressive behavior on the road. These findings emphasize the importance of stress management as a psychological intervention to reduce aggression and contribute to reducing traffic accident rates. Keywords: Aggressive Driving Behavior, Coping Stress, Z Generation